Assessment of job satisfaction among staff at Yas Hospital complex and its relation with demographic factors: Validation of the Yas Job Satisfaction Questionnaire - Pegah Salimi pormehr; Mani Yousefvand; Mahnaz Mirsane; Naser Yousefzadeh kandovani (Tehran University of Medical Sciences, 2021)
Background and Objectives: the  purpose of this study was to assess the validity and reliability of the Yas Job Satisfaction Questionnaire in order to develop a useful tool for measuring and evaluating job satisfaction among Yas Hospital Complex staff. Materials and Methods: Face validity, content validity ratio, and content validity index were used to evaluate the questionnaire's validity and reliability. Cronbach's alpha and the halving technique were used among 150 medical personnel in this cross-sectional study The key elements of the final questionnaire were four dimensions of leadership style, job nature, reward system, performance appraisal, and organizational climate.To report the mean of quantitative variables at different levels, qualitative factors were evaluated and analyzed using analysis of variance (ANOVA). Results: There were 111 females and 39 males among the 150 participants. The content validity ratio and content validity index were both acceptable.Cronbach's alpha method reported a reliability of 0.92 for the questionnaire, indicating that the internal reliability is acceptable.The lowest level of satisfaction was in the leadership style dimension, with an average of 10.53 4.91, while the highest level of satisfaction was in the job nature dimension, with an average of 21.24 7.05. Conclusion: The Yas Job Satisfaction Questionnaire has acceptable validity and reliability to assess the level of job satisfaction among medical staff, according to the findings of this study. Furthermore, job satisfaction was moderate in most of the dimentions surveyed.